Causally mapping human threat extinction relevant circuits with depolarizing brain stimulation methods. (January 2023) - Webler, Ryan D.; Oathes, Desmond J.; van Rooij, Sanne J.H.; Gewirtz, Jonathan C.; Nahas, Ziad; Lissek, Shmuel M.; Widge, Alik S.
Abstract: Laboratory threat extinction paradigms and exposure-based therapy both involve repeated, safe confrontation with stimuli previously experienced as threatening. This fundamental procedural overlap supports laboratory threat extinction as a compelling analogue of exposure-based therapy. Threat extinction impairments have been detected in clinical anxiety and may contribute to exposure-based therapy non-response and relapse. However, efforts to improve exposure outcomes using techniques that boost extinction – primarily rodent extinction – have largely failed to date, potentially due to fundamental differences between rodent and human neurobiology. In this review, we articulate a comprehensive pre-clinical human research agenda designed to overcome these failures. We describe how connectivity guided depolarizing brain stimulation methods (i.e., TMS and DBS) can be applied concurrently with threat extinction and dual threat reconsolidation-extinction paradigms to causally map human extinction relevant circuits and inform the optimal integration of these methods with exposure-based therapy. We highlight candidate targets including the amygdala, hippocampus, ventromedial prefrontal cortex, dorsal anterior cingulate cortex, and mesolimbic structures, and propose hypotheses about how stimulation delivered at specific learning phases could strengthen threat extinction. Highlights: Impaired threat extinction may contribute to exposure-based treatment failure. Efforts to strengthen exposure-based therapy response by boosting threat extinction have largely fallen short. Preclinical studies that apply TMS and DBS during specific threat extinction/reconsolidation stages could inform the integration of circuit-based treatments with exposure-based therapy.